Seasonal rubisco enzyme activities and caulerpenyne levels in invasive Caulerpa racemosa var. cylindracea and native Caulerpa prolifera - CAVAS, L.; CENGIZ, S.; ABIDIN KARABAY, Z. (Mediterranean Marine Science, 2012)
Caulerpa racemosa var.cylindracea (C.racemosa) is an invasive marine seaweed in the Mediterranean Sea. Since no valid eradication method has been existed in the scientific literature on this species, it has currently been continuing its invasion along the coastlines of 13 Mediterranean countries. One of the important factors responsible for its invasion is thought as its toxic secondary metabolite, caulerpenyne (CYN). The present paper investigates seasonal changes in the secondary metabolite CYN, and rubisco enzyme (EC 4.1.1.39) activities of the invasive C. racemosa and native C. prolifera. Inasmuch as no correlation between CYN level and rubisco enzymic activity was observed in these species, it is considered that the regulation of CYN synthesis caulerpenyne and rubisco enzymic activity might be controlled independently. In conclusion, the further analysis on the rubisco enzymic activity determinations with MEP and mevalonate pathway which are considered responsible for CYN bio-synthesis should be studied in great detail in invasive and native Caulerpa species in the Mediterranean Sea to get the overall picture.